CLINICAL EFFICACY OF ORAL AZITHROMYCIN VERSUS OTHER ANTIMICROBIAL DRUGS IN THE TREATMENT OF TYPHOID PATIENTS ACROSS ALL AGE GROUPS: A SYSTEMATIC REVIEW OF RANDOMIZED CONTROLLED TRIALS - Muhammad Uzair; Saad Wali; Anees Ur Rehman; Afaq Ahmad; Muhammad Hamza Rafique; Muhammad Bilal Nadeem (Journal of Ayub Medical College Abbottabad, 2024)
Background: Typhoid is a major health concern. Drug-resistant cases of typhoid have given rise to new debates. Azithromycin has shown adequate results. The study is designed to determine the clinical efficacy of oral azithromycin versus other antimicrobial drugs in typhoid patients. Method: The studies included in the systematic review are randomized controlled trials, comparing the clinical efficacy of azithromycin to other antimicrobial drugs on typhoid patients. We searched 1180 articles from Google Scholar, PubMed Central, Cochrane Library, PLOS ONE, and JSTOR on 16th October, 2023. The risk of bias was analyzed by visualizing the funnel plot, Begg’s and Egger’s test, and plotting risk of bias graphs. Forest plots are created to display the findings. Results: We identified 14 research articles (1556 participants). Odds ratios of the treatment outcomes were extracted. In a forest plot, the overall effect of the treatment outcome (CI=95%) of azithromycin, in comparison to fluoroquinolones appeared to be favourable (Random Effect Model (REM)=2.15, heterogeneity: I2=37%, Ï„2= 0.1729, p=0.15, the overall pooled effect was towards right side). Compared to chloramphenicol, azithromycin showed a high odds ratio (1.23). However, there was no difference in outcome among ceftriaxone and azithromycin groups (REM=0.67, heterogeneity: I2=0%, Ï„2=0%, p=0.78, the overall pooled effect touched the no-effect line). Conclusion: Azithromycin is more clinically efficacious than fluoroquinolones and chloramphenicol. The drug has fewer documented relapses in comparison with other antimicrobial drugs. Fever clearance time of azithromycin is greater than ceftriaxone and chloramphenicol.